Technological and Socio‐Demographic Factors Influencing Telemedicine Literacy in Trinidad and Tobago: A Cross‐Sectional Study Using Multidimensional Approach - Ngozika E. Ezinne; Isaac Koomson; Anayochukwu E. Anyasodor; Ellen K. Antwi‐Adjei; Dipesh Bhattarai; James Armitage; Uchechukwu L. Osuagwu (Health Science Reports)
ABSTRACT Background and Aims The COVID‐19 pandemic restriction impacted physical or face‐to‐face interactions, leading to an upsurge in the use of information technology (IT). This necessitated the adoption of various remote healthcare services including telehealth. This study aimed to examine the role of technological and socio‐demographic factors in enhancing telemedicine literacy. Methods This cross‐sectional study was conducted in Trinidad and Tobago (T&T) in 2022 involving 528 participants. The study employed the Alkire‐Foster multidimensional method to measure the telemedicine literacy of participants. The multidimensional telemedicine literacy index was constructed using nine indicators spread across three dimensions (i.e., knowledge, attitude/perception, and practice dimensions), where a threshold of 0.5 was employed to identify those with adequate knowledge to be considered literate in telemedicine. The technological component was captured using IT ability. Participants completed a 31‐item questionnaire administered electronically via iPads. A “Yes” response was coded as 1 and “No” as 0. Results Most respondents (62%) were aged 21–40, with 60% identifying as female. Most were Afro‐Trinidadian (54.46%), urban residents (84%), employed (80%), and earned a high income (87%). Overall, participants demonstrated a high perceived IT ability, with a mean score of 0.918 (SD = 0.27). Urban residents exhibited IT skills that were 10% superior to those of rural residents; however, this did not necessarily translate into higher telemedicine literacy. Gender differences were observed, with males reporting IT skills 3% higher than females. Notably, IT ability was a significant predictor of telemedicine literacy, particularly among females and urban residents. Additionally, individuals with postgraduate qualifications, Indo‐Trinidadians, and Christians exhibited significantly higher telemedicine literacy. Conclusions This study emphasizes the pivotal role of IT ability in telemedicine literacy across varied socio‐demographic groups in T&T. To promote healthcare for all, interventions targeting digital literacy are crucial to ensure equitable access and enhance the reach of telemedicine in T&T.